Tradisi Pecah Telur dalam Adat Pernikahan Masyarakat Jawa di Desa Sait Buttu Saribu, Kabupaten Simalungun - Awaliyah, Afsah; Rohani, Laila; Batubara, Abdul Karim (Warisan: Journal of History and Cultural Heritage, 2020)
This article discusses the egg breaking tradition carried out by the Javanese people who live in Sait Buttu Saribu Village, Simalungun Regency. The migration of the Javanese to East Sumatra in the 19th century, to work on plantations owned by Dutch businessmen, was accompanied by a shift in traditions and culture that they had practiced so far. This research uses qualitative research methods, with a cultural anthropological approach. This approach focuses on the view of life of a group of people in the form of behavior, beliefs, values and symbols that they inherit through the communication process from one generation to the next. After living for a long time in the Simalungun area, the Javanese people in this area still practice the egg breaking tradition, but it has been elaborated according to local culture. This tradition is usually carried out after the bride and groom carry out the marriage contract. In the procession, usually the bridegroom will step on a bamboo board under which is a raw egg. The foot used to step on the egg is the right foot, because the Javanese believe the right is a symbol of goodness